Co-movements and causalities between ethanol production and corn prices in the USA: New evidence from wavelet transform analysis. (15th November 2022) - Bilgili, Faik; Kocak, Emrah; Kuskaya, Sevda; Bulut, Umit
Abstract: The literature has been increasingly examining the existence of possible compatibility or conflict hypotheses between biofuels and food security in recent years. While current research outputs do not provide a consensus, the new evidence can guide sustainable development policies. In this context, this paper investigates the co-movements between fuel ethanol production and corn prices for the US employing oil production, population, and real exchange rate control variables via the Morlet wavelet analysis from 1990:m1 to 2021:m4. The results of the analysis provide empirical evidence for the dynamics of the relationship between ethanol production and corn prices in the short and long term. However, the striking output of this paper is that increases in corn prices have followed increases in fuel ethanol production in the US markets since 2010. Especially in the long-term (from 2010:m3 to 2019:m12), the increase in ethanol production caused an increase in corn prices. From a sustainable development perspective, this paper points to the existence of a conflict between ethanol production and corn prices in the US over the past decade. Highlights: Explores the existence of compatibility or contradiction hypotheses between ethanol production and corn prices. Employs Morlet wavelet analysis. Since 2010, increases in fuel ethanol production are followed by increases in corn prices in the US. Confirms the existence of a conflict between ethanol production and corn prices.